OPTIMIZATION OF MANPOWER IN SEAMLESS PIPE THREADING MANUFACTURE BATAM - Engelin Manopo, Maya; Khaddafi, Muammar; Indrayani, Indrayani (RADJA PUBLIKA, 2022)
The objective of manpower optimization is to have the right number of workers with the right capabilities in the right production areas. In this research, a model was developed for optimizing manpower allocation coupling threading area. Total initial manpower allocation is 26 manpower. Improvement executed which consider to customer demand and production capability. Evaluation result indicates there is unbalance workload distribution of each manpower. Improvement planned such as balancing the work load of each manpower, machine replacement, and re-layout the production area. The implementation based on Direct Productivity formula resulted manpower saving cost about 50%, from 26 manpower to 16 manpower. Standardized work did as well as the control item in order to stabilize the improvement process. The next step is the analysis of production capability to face the increasing of customer demand. This analysis concluded that production needed additional overtime and additional work shift in order to fulfill the customer demand